PENGARUH JARAK TANAM DAN BERBAGAI DOSIS KOMPOS TKKS TERHADAP PERTUMBUHAN SERTA PRODUKSI KACANG PANJANG RENEK (Vigna unguiculata var. sesquapedalis ) - Ari Suwandi; Siti Zahrah; Fathurrahman, F. (DINAMIKA PERTANIAN, 2019)
This study was conducted to determine the interactions and main effects on the implementation of planting distance and the addition of oil palm empty fruit bunch OPEFB compost on the growth and production of dwarf bean (Vigna unguiculata var. sequapedalis). This work was conducted using a completely randomized design factorial, consisting of two factors. The first J factor (planting distance) consisted of 4 treatment levels 50 cm x 30 cm, 55 cm x 35 cm, 60 cm x 40 cm, 65 cm x 45 cm and T factor (OPEFB compost) consisted of 4 treatment levels 0, 1.5, 2 and 2.5 kg per plot. The parameters observed were plant height (cm), age of flowering day after planting (HST), age of harvest (HST), number of pods, pod length (cm), pod weight (g) and number of remaining pods. Observation data were analyzed statistically and a BNJ test of 5% was performed. The results showed that the interaction between planting distance and addition of OPEFB compost had a significant effect on all parameters observed with the best combination of 65 x 45 cm and OPEFB compost 2.5 kg per plot. The main effect gave a significant on all parameters with the best treatment of 65 x 45 cm, while the best pod weight parameter of 60 x 40 cm. The main effect on OPEFB compost had also a significant effect on all parameters with the best treatment at 2.5 kg per plot.